(untitled) (FAVE Sección Ciencias Veterinarias, 2017)
The aim of this work was to study the epidemiology of gastrointestinal nematodes (GIN) on beef cattle in the Chaco Serrano region of northwestern Argentina, during the periods May-Sept. 2014 and May -March 2015-16. During each period, three groups of 17 heifer calves were performed: STG: calves treated every 45-50 days with moxidectin, LTG: calves treated once, June/2014 ivermectin and July/2015 doramectin and UTG: untreated calves. Eggs per gram of feces (epg) and feces cultures were performed. Live weight gain (LWG) was recorded. At the start of both periods the mean calf epg was moderate (=515±449, 2014; =484±464, 2015) and peaks towards late autumn, to decrease forward the spring. LTG epg post treatment only decreases partially and STG epg always showed negligible values. Predominant genera were Cooperia (41.8%) and Haemonchus (53.7%). In both periods, the treatment effect was evident from the winter, showing STG a significant (p<0.05) higher LWG than the other groups when the ranch increased the alimentary offer. At the end of the trial, average total LWG were in kg, 11.2, 11.5 and 19.6 (2014) and 54.3, 56.5 and 73.4 (2015) respectively for NTG, LTG y el STG.